Intracardiac versus transesophageal echocardiography for diagnosis of left atrial appendage thrombosis in atrial fibrillation: A meta‐analysis. Issue 10 (3rd September 2021) - He, Guijun; Liu, Hanxion; Huang, Xiaoyu; Deng, Xiaoqi; Yang, Guosu; Luo, Duan; Cai, Lin
Abstract: Introduction: Left atrial appendage (LAA) thrombus in patients with atrial fibrillation is usually detected by transesophageal echocardiography (TEE). Intracardiac echocardiography (ICE) can be a suitable alternative to detect thrombosis. However, the effectiveness of the two methods for detecting LAA thrombus is still unclear, we performed a meta‐analysis that compared ICE versus TEE for LAA thrombosis. Methods: We searched PubMed, Cochrane Library, and Embase for published abstracts and manuscripts on June 1, 2020. The analysis was performed using RevMan 5.3, STATA 15, and Meta‐Disc 1.4. Results: Eight studies consists of 1108 patients (TEE = 558 vs. ICE = 550) were included. The average sensitivity of ICE and TEE to diagnose LAA thrombus is 1.0 (95% CI: 0.91–1.00) versus 0.68 (95% CI: 0.49–0.83), and specificity of ICE and TEE to diagnosis of LAA thrombus is 1.0 (95% CI: 0.99–1.00) versus 0.98 (95% CI: 0.96–0.99). The AUC of ICE and TEE is 0.9846 (SEAUC = 0.0196) and 0.9655 (SEAUC = 0.0401), and the Q* statistics is 0.9462 (SEQ* = 0.0406) and 0.9127 (SEQ * = 0.0616), respectively. Z test was performed on Q* statistics (Z = 0.45, p  > .05). Conclusion: The ICE and TEE have similar diagnostic efficacy for LAA thrombosis, but the ICE has higher sensitivity. Compared with TEE, ICE may be more advantages and prospects for clinical application.